KOMUNIKASI PENDAMPING PROGRAM KELUARGA HARAPAN (PKH) DALAM PENCEGAHAN STUNTING DI KABUPATEN JENEPONTO - Ibrahim, Rayes; Farid, Muhammad; Arianto; Alimuddin Unde, Andi (Program Studi Ilmu Komunikasi FISIP UM Buton, 2024)
This research aims to find out the appropriate communication strategies that PKH Facilitators can use to prevent stunting in Jeneponto Regency. using qualitative research methods, namely conducting interviews with PKH Facilitators, Beneficiary Families (KPM), Observers and the relevant Government. The results of the research reveal the strategies of social assistants in preventing stunting in Jeneponto Regency Keywords: Communication, Strategy Communication, Stunting Prevention, PKH Social Assistance